Democratic governance (Studi mengenai governability dalam pengembangan UMKM berbasis e-commerce di Kota Yogyakarta) - Nugroho, Hanantyo Sri (Universitas Medan Area, 2018)
Â The development of technological progress has had a significant impact on. The impact is the same access to information that flows very quickly and easily. Alternative,. Changes in the centralistic direction towards decentralization. Of course, this is in accordance with the spirit of local economic development at the regional level. This study uses a qualitative approach, where the main question that arises is how to achieve local economic development. Based on this, it is necessary to make efforts to spur economic growth in exploiting the market. Later, this research is focused on the role of government in conducting program of empowerment of UMKM based on e-commerce, and role of government in using dialogue room. Therefore, the target of this research is the UMKM which has been assisted by the government through e-commerce. Based on this, the formulation of the problems that are built is 1) How the role of local government of Yogyakarta in the development of UMKM based e-commerce, 2) How the quality of the use of space dialogue in the development of UMKM-based e-commers. This research uses qualitative approach. The result of this research is the ability of government in developing UMKM with linear e-commerce based on democratic governance quality, that is empowerment and p